1994
DOI: 10.1002/eji.1830241044
|View full text |Cite
|
Sign up to set email alerts
|

Staurosporine restores signaling and inhibits interleukin‐8‐induced chemotactic desensitization

Abstract: Interleukin 8 (IL-8) is a chemotactic cytokine (chemokine) that plays a key role in the accumulation and activation of neutrophils at inflammatory sites. In this report we demonstrate that homologous chemotactic desensitization occurs upon pretreatment of neutrophils with IL-8 or N-formyl-methionyl-leucyl-phenylalanine (FMLP) and results in the inhibition of neutrophil chemotaxis upon subsequent challenge with the same ligand. This homologous chemotactic desensitization could be prevented by pretreating the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Upon stimulation of the neutrophils with IL-8, its receptors become desensitized and are less susceptible to subsequent restimulation with IL-8. Desensitization results in a decreased migration and phosphorylation of IL-8 receptor targets [50]. A recent study has suggested that in MDS patients, serum levels of IL-8 are elevated [51].…”
Section: Discussionmentioning
confidence: 99%
“…Upon stimulation of the neutrophils with IL-8, its receptors become desensitized and are less susceptible to subsequent restimulation with IL-8. Desensitization results in a decreased migration and phosphorylation of IL-8 receptor targets [50]. A recent study has suggested that in MDS patients, serum levels of IL-8 are elevated [51].…”
Section: Discussionmentioning
confidence: 99%
“…Cells were treated with 10 lM BB for 12 h. In some cases, to test if the effects of BB on APP processing were associated with modulation of the PI3K pathway, LY294002 (10 lM) was also added to the medium 30 min prior to the addition of BB [8,12,15]. To test whether GSK3b, a downstream target of the PI3K pathway, was involved in BB regulation of APP processing, cells were treated with 30 lM SB 415286, a known GSK3 inhibitor, for 12 h. In all experiments, an equivalent volume of vehicle was added to control cultures.…”
Section: Reagentsmentioning
confidence: 99%
“…This could be explained by prior desensitisation of the peripheral blood neutrophils with IL-8 [5,6]. Since serum IL-8 was not increased, it can be speculated that the concentration of IL-8 produced by activated endothelium [16] in the synovial tissue was high enough to desensitise the passing neutrophils.…”
Section: Discussionmentioning
confidence: 97%
“…IL-8 stimulation of neutrophils was performed to examine whether homologous desensitisation for IL-8 was present, as has been reported to occur in vitro [5,6]. …”
Section: Introductionmentioning
confidence: 99%